Synapse formation and preferential distribution in the granule cell layer by regenerating retinal ganglion cell axons guided to the cerebellum of adult hamsters - Zwimpfer, TJ (J Neurosci, 1992)
To investigate constraints and preferences for synaptogenesis in the injured mammalian CNS, regenerating retinal ganglion cell (RGC) axons of adult hamsters were guided through a peripheral nerve (PN) graft to a target they do not usually innervate: the cerebellum (Cb). When identified by the presence of HRP anterogradely transported from the retina 2–9 months later, such RGC axons were found to have extended into the cerebellar cortex for up to 650 microns. Most of this growth was in the granule cell layer (GCL) and only a few axons entered the molecular layer. The preference for the GCL could not be explained by the position of the PN graft in the Cb, a selective denervation of the GCL, local damage to other neurons, or the distribution of reactive gliosis in the vicinity of the graft. Furthermore, by EM, more than 95% of the labeled retinocerebellar terminals and synapses were in the GCL. Retinocerebellar terminals were larger and contained more synapses than the regenerated RGC terminals previously studied in the superior colliculus. These results indicate that regenerating axons of CNS neurons can form persistent synapses with novel targets. The preferential synaptogenesis in the GCL suggests that such unusual connections are not formed randomly in the CNS of these adult mammals.